The Assistance of Elementary School Teacher Assessment Technique in Online Learning - Gamar Al Haddar (International Journal of Community Engagement Payungi, 2023)
Assessment is always carried out in every teaching and learning activity. Assessment is the collection of information to measure the achievement of a person's results after participating in teaching and learning activities. Assessment in learning activities is not only the final achievement but the process also needs to be assessed. During the Covid-19 Pandemic, the assessment is now done online. Teacher assessment during the COVID-19 pandemic is the most important point that must be explored and studied. The goal is that teachers have a deep understanding to carry out assessment techniques during the COVID-19 pandemic.  The researchers used Participation Action Research (PAR) in giving assessment and  The assessment given to students by the teacher is not only a cognitive assessment, but also includes affective and psychomotor aspects. The implementation of this community service would be carried out in March 2021 online via zoom. The target of the activity is elementary school level teachers. Assessment techniques that can be carried out by teachers in online learning vary. Knowledge assessment can be done through written tests, oral tests and various assignments. Skills assessment can be done through practice, products, projects and portfolios. The attitude assessment technique in online learning can be done by self-assessment through questionnaires and journals filled out by students.